2017
DOI: 10.1016/j.apenergy.2017.05.132
|View full text |Cite
|
Sign up to set email alerts
|

Value of gas network infrastructure flexibility in supporting cost effective operation of power systems

Abstract: The electricity system balancing is becoming increasingly challenging due to the integration of Renewable Energy Sources (RES). At the same time, the dependency of electricity network on gas supply system is expected to increase, as a result of employing flexible gas generators to support the electricity system balancing. Therefore the capability of the gas supply system to deliver gas to generators under a range of supply and demand scenarios is of a great importance. As potential solutions to improve securit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 20 publications
2
48
0
Order By: Relevance
“…is the profit of agent (i), x g the vector of gas variables, x (i) g the sub-vector (of vector x g ) of gas variables that pertains to agent (i), λ g , µ g vectors of dual gas variables, λ (i) g the sub-vector (of vector λ g ) of dual gas variables that pertains to agent (i), x e the vector of power variables, x (i) e the sub-vector (of vector x e ) of power variables that pertains to agent (i), λ e , µ e vectors of dual power variables, λ (i) e the sub-vector (of vector λ e ) of dual power variables that pertains to agent (i), o g the gas offer/bid vector, o Upper-level problem (1) and (2) represents the profit of the agent (revenue minus cost for a producer and utility minus payment for a consumer), while lower-level problems (3)-(5) and (6)- (8) represent the clearing of the gas and power markets, respectively.…”
Section: Single-agent Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…is the profit of agent (i), x g the vector of gas variables, x (i) g the sub-vector (of vector x g ) of gas variables that pertains to agent (i), λ g , µ g vectors of dual gas variables, λ (i) g the sub-vector (of vector λ g ) of dual gas variables that pertains to agent (i), x e the vector of power variables, x (i) e the sub-vector (of vector x e ) of power variables that pertains to agent (i), λ e , µ e vectors of dual power variables, λ (i) e the sub-vector (of vector λ e ) of dual power variables that pertains to agent (i), o g the gas offer/bid vector, o Upper-level problem (1) and (2) represents the profit of the agent (revenue minus cost for a producer and utility minus payment for a consumer), while lower-level problems (3)-(5) and (6)- (8) represent the clearing of the gas and power markets, respectively.…”
Section: Single-agent Modelmentioning
confidence: 99%
“…However, tools to comprehend the effect of such interdependency are limited. Many of these tools adopt a centralized perspective, in which a single operator manages both the gas and power systems [3][4][5][6][7][8][9][10][11][12][13][14] , which is unrealistic. Representative references are briefly discussed below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second group of studies proposes stylized models that focus on interdependencies between different energy sectors, e.g., the power and gas sectors. These models reduce complexity by limiting the considered energy sectors, which allows for considering further technical constraints [20][21][22][23][24][25], considering strategic behavior [26] or dealing with uncertainties by using various methods like stochastic programming. An example of using integrated models to study the interdependencies between the gas and electricity sector can be found in [21], where the authors investigate disruption scenarios based on an exemplary network topology.…”
Section: Introductionmentioning
confidence: 99%
“…Geographical and functional infrastructure interdependence between the national electricity grid (left) and the gas transmission infrastructure (right) for Great Britain.Figure adaptedfrom Reference[243].…”
mentioning
confidence: 99%